A 100 Mpc2 Structure Traced by Hyperluminous Galaxies around a Massive z = 2.85 Protocluster - George C.P. Wang; Scott C. Chapman; Nikolaus Sulzenauer; Frank Bertoldi; Christopher C. Hayward; Ryley Hill; Satoshi Kikuta; Yuichi Matsuda; Douglas Rennehan; Douglas Scott; Ian Smail; Charles C. Steidel (The Astrophysical Journal)
We present wide-field mapping at 850 μ m and 450 μ m of the z = 2.85 protocluster in the HS 1549+19 field using the Submillimetre Common-User Bolometer Array 2. Spectroscopic follow-up of 18 bright sources selected at 850 μ m, using the Northern Extended Millimeter Array and Atacama Large Millimeter/submillimeter Array, confirms that the majority lie near z  ≃ 2.85 and are likely members of the structure. Interpreting the spectroscopic redshifts as distance measurements, we find that the submillimeter galaxies (SMGs) span 123 pMpc ^2 in the plane of the sky and demarcate a 3600 pMpc ^3 “pancake”-shaped structure in three dimensions. We find that the high star formation rates of these SMGs result in a total star formation rate of 20,000 M _⊙ yr ^−1 from just the brightest galaxies in the protocluster. These rapidly star-forming SMGs can be interpreted as massive galaxies growing rapidly at large clustercentric distances before collapsing into a virialized structure. We find that the SMGs trace the Ly α surface density profile. Comparison with simulations suggests that HS 1549+19 could be building a structure comparable to the most massive clusters in the present-day Universe.